International Conferences and Chemicals’ Traffic Control Regulation - I. V. Esin (Московский журнал международного права)
The demands of the world social and economic challenges require active utilization of chemical substances. Developing of the international economic order and global commodities market has raised an intergovernmental point of control over the chemicals’ turnover and their environmental impact. The countries have acknowledged that it is vital to work out general principles of cross-border chemicals’ traffic control regulation by developing a new international legal framework.In the article are analyzed the history and progress of the chemicals’ traffic control regulation being sequentially worked out in the acts of international conferences: Stockholm Declaration (1972), Rio-de-Janeiro Declaration and Agenda 21(1992), Plan of Implementation of the World Summit on Sustainable Development (2002) and the Strategic Approach to International Chemicals Management (SAICM) (2006).